2021
DOI: 10.1126/sciadv.abj9446
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of human cortical folding

Abstract: The first genome-wide study of sulcal depth shows that it is highly genetically discoverable, associated with neurodevelopment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 69 publications
10
62
0
Order By: Relevance
“…This suggests that MOSTest may prioritise variants which have more strongly aligned effect alleles in relation to the genome-wide average. Further, the recent findings of pleiotropic genetic effects on brain structure and function (van der Meer et al, 2021; Roelfs et al, 2022; Shadrin et al, 2021), as well as patterns of widespread gene expression across different brain regions (Hawrylycz et al, 2015) underscore the highly inter-related functions of brain regions and structures. Taken with our findings, this indicates that a complex interplay between heritable brain functions result in patterns of heritable, inter-related, higher-order mental traits which contribute to the core characteristics of an individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that MOSTest may prioritise variants which have more strongly aligned effect alleles in relation to the genome-wide average. Further, the recent findings of pleiotropic genetic effects on brain structure and function (van der Meer et al, 2021; Roelfs et al, 2022; Shadrin et al, 2021), as well as patterns of widespread gene expression across different brain regions (Hawrylycz et al, 2015) underscore the highly inter-related functions of brain regions and structures. Taken with our findings, this indicates that a complex interplay between heritable brain functions result in patterns of heritable, inter-related, higher-order mental traits which contribute to the core characteristics of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…A boost in genetic discovery has also been demonstrated by the "pleiotropy-informed" multivariate omnibus statistical test (MOSTest). Applying MOSTest to brain imaging phenotypes has shown that alterations in brain morphology and functional connectivity are associated with hundreds of genetic loci with "pleiotropic" genetic effects across the brain, even despite weak genetic correlation (van der Meer et al, 2020a(van der Meer et al, , 2021Roelfs et al, 2022;Shadrin et al, 2021). We hypothesised that the genetic architecture of interconnected higher-order mental traits, such as cognition and personality are driven by similar pleiotropic effects.…”
mentioning
confidence: 99%
“…Recent work revealed a distributed genetic architecture of human brain anatomy 24 , 25 and function 26 and suggested that capitalizing on this distributed nature in a multivariate GWAS approach can significantly improve the discovery beyond standard GWAS approaches 24 . Advancements into deriving subdivisions of the hippocampus through adaptive segmentation has allowed for a fine-grained assessment across multiple subregions 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that many brain imaging and genetics studies of structural brain features regress out global measures 42,43 , this study provides a more nuanced view of how global measures add to our interpretation of the genetics underlying brain morphology. The overlap in genetic architecture between global measures and multiple distributed brain regions could also be further elucidated with multivariate methods in future work, given its success in boosting discovery of novel genetic variants underlying cortical morphology [44][45][46] . Understanding global as compared to regional patterns of cortical morphology can have important implications for our understanding of higher cognitive function 47 and in turn, psychiatric and neurological disorders that impact such cognitive processes.…”
Section: Discussionmentioning
confidence: 99%